Identification of voters with interest groups improves the electoral chances of the challenger - Vjollca Sadiraj; Jan Tuinstra; Frans van Winden (Center for Economic Studies and ifo Institute (CESifo), 2010)
Interest groups are introduced in a spatial model of electoral competition between two political parties. We show that, by coordinating voting behavior, these interest groups increase the winning set, which is defined as the set of policy platforms for the challenger that will defeat the incumbent. Therefore interest groups enhance the probability of the challenger winning the election.
Keywords: D71; D72; 330; spatial voting models; electoral competition; winning set; interest groups; Wahlkampf; Wahlverhalten; Interessenvertretung; Public Choice; Theorie